Odpowiedź :
Odpowiedź:
A.
a)
7 + 5 = 12
b)
-2 + (-7) = -2 - 7 = -9
c)
-4 + (-8) = -4 - 8 = -12
d)
-2 + (-1) = -2 - 1 = -3
e)
-6 + (-9) = -6 - 9 = -15
f)
4 + 8 = 12
g)
-5 + (-9) = -5 - 9 = -14
h)
-7 + (-6) = -7 - 6 = -13
i)
-3 + (-2) = -3 - 2 = -5
B.
a)
7 + (-7) = 7 - 7 = 0
b)
-2 + 2 = 0
c)
8 + (-8) = 8 - 8 = 0
d)
1 + (-1) = 1 - 1 = 0
e)
-11 + 11 = 0
f)
-18 + 18 = 0
g)
9 + (-9) = 9 - 9 = 0
h)
-17 + 17 = 0
i)
-3 + 3 = 0
C.
a)
7 + (-5) = 7 - 5 = 2
b)
-2 + 7 = 5
c)
4 + (-8) = 4 - 8 = -4
d)
-2 + 1 = -1
e)
6 + (-9) = 6 - 9 = -3
f)
8 + (-4) = 8 - 4 = 4
g)
-5 + 9 = 4
h)
-7 + 6 = -1
i)
3 + (-2) = 3 - 2 = 1
D.
a)
7 + (-3) = 7 - 3 = 4
b)
-2 + (-6) = -2 - 6 = -8
c)
4 + (-4) = 4 - 4 = 0
d)
-2 + 9 = 7
e)
-8 + (-9) = -8 - 9 = -17
f)
11 + (-11) = 11 - 11 = 0
g)
-5 + 4 = -1
h)
-3 + (-6) = -3 - 6 = -9
i)
5 + (-5) = 5 - 5 = 0
E.
a)
-234 + 123 + (-20) = -234 + 103 = -131
b)
-54 + (-72) + (-63) = -54 - 72 - 63 = -117 - 72 = -189
c)
-45 + 78 + (-15) + (-40) + 22 = -60 + 78 - 18 = -60 + 60 = 0
d)
17 + (-28) + (-13) + 42 + (-5) = -11 + 29 - 5 = -16 + 29 = 13
Szczegółowe wyjaśnienie: